Biosynthesis of ascites sialoglycoprotein-1, the major o-linked glycoprotein of 13762 rat mammary adenocarcinoma ascites cells - Spielman, Julie; University of Miami (1987)
Ascites sialoglycoprotein-1 is postulated to act as an anti-recognition factor, preventing destruction of tumor cells by host immune effectors. Because ASGP-1 contains 70% by weight O-linked carbohydrate it also provides a good model for investigating events in biosynthesis of O-linked glycoproteins. These events are not well-understood, mainly due to lack of appropriate inhibitors for initiation and elongation of oligosaccharides. The structures of the major oligosaccharides of ASGP-1 have been characterized previously (Hull et al., 1984). The present studies were undertaken to determine the timing of the major events in biosynthesis, and to characterise the contributions of chain initiation and elongation in maturation of the glycoprotein. Initiation of the earliest O-linked chains was detected by analysis of conversion of $\sp3$H-thr to $\sp3$H 2-aminobutyrate following mild alkaline borohydride elimination of O-linked sugars from peanut lectin-precipitated ASGP-1.
Initiation was detected within 5 min of translation; amino sugar analysis of GlcNH$\sb2$-labeled, trypsinized cells also showed that GalNAc was added as late as 5 min prior to arrival of ASGP-1 at the cell surface. Thus initiation occurs throughout biosynthesis. Maturation of the glycoprotein from a lightly-glycosylated immature form to the heavily-glycosylated mature form involved both continued initiation of new chains and chain elongation, and occurred with a half-time of about 30 min. Analysis of labeled ASGP-1 released from the cell surface by trypsinization showed that although some newly-synthesized ASGP-1 reached the cell surface within 70-80 min of protein synthesis, the half-time for appearance of mature glycoprotein was in excess of 4 hr, indicating that most molecules reside in an intracellular compartment(s) for a considerable time.
Maturation of ASGP-1 can be altered by monensin, which retards $\beta
(UnM)AAI8813703
Source: Dissertation Abstracts International, Volume: 49-05, Section: B, page: 1682.
Supervisor: Kermit L. Carraway.
Thesis (Ph.D.)--University of Miami, 1987.
Microfiche.
Keywords: Chemistry, Biochemistry